Re-orienting Victorian Studies: A European Perspective - Jedrzejewski, Jan (Australasian Journal of Victorian Studies, 2011)
Approaching Victorian literature from a Continental European perspective is not, it might seem, the most obvious way of trying to re-orient Victorian studies: not only is popular perception of English literature across Europe shaped, largely, by the works of leading Victorian novelists such as Dickens and the Brontës, but Continental European critics have also, over the last century or so, offered a number of very significant contributions to the study of the literature and culture of the Victorian period. Indeed, one of the most influential early studies of Victorian fiction was written in French: Louis Cazamian’s Le Roman social en Angleterre, 1830-1850 was published as early as in 1903, though it was not translated into English until 1973.